2019
DOI: 10.1007/s11418-019-01301-y
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Ceramicines M–P from Chisocheton ceramicus: isolation and structure–activity relationship study

Abstract: The article Ceramicines M–P from Chisocheton ceramicus: isolation and structure–activity relationship study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It took 6 more years before another study reported the identification of four new compounds, ceramicines M–P, which are noncytotoxic molecules endowed with a marked capacity to reduce lipid droplet accumulation (LDA) in mouse preadipocyte cells. [ 43 ] The anti‐LDA activity of ceramicines is discussed further below. Then, more recently, two studies completed the alphabet with the discovery of ceramicines Q–T in 2023 and ceramicines U–Z in 2024.…”
Section: Phytochemicals Isolated From C Ceramicusmentioning
confidence: 99%
See 2 more Smart Citations
“…It took 6 more years before another study reported the identification of four new compounds, ceramicines M–P, which are noncytotoxic molecules endowed with a marked capacity to reduce lipid droplet accumulation (LDA) in mouse preadipocyte cells. [ 43 ] The anti‐LDA activity of ceramicines is discussed further below. Then, more recently, two studies completed the alphabet with the discovery of ceramicines Q–T in 2023 and ceramicines U–Z in 2024.…”
Section: Phytochemicals Isolated From C Ceramicusmentioning
confidence: 99%
“…The removal of this hydroxyl group as in 7‐dehydroxyceramicine B ( 6 ) also reduced the activity (IC 50 : 4.7 µM), as well as the change of the anomery in the case of 7‐ epi ‐ceramicine B ( 7 ) (IC 50 : 12.2 µM) (Figure 5) and other derivatives with a 7β‐OR substituent. [ 43 ] Synthetic approaches have been deployed to build the skeleton ring system characteristic of Meliaceae limonoids and occasionally to achieve the total synthesis of selected limonoids, [ 3,20,110 ] but more work is needed in the ceramicine series to prepare novel analogs. The marked anti‐LDA activity of ceramicine B should encourage the design of novel compounds.…”
Section: Hemisynthetic Ceramicine Derivativesmentioning
confidence: 99%
See 1 more Smart Citation